#### Answer

$g(x)=-(x-2)^2+1=-x^{2}+4x-3$

#### Work Step by Step

We obtain $g(x)$ by reflecting $f(x)=x^2$ about the $x$-axis and shifting right 2 units and up 1 unit, i.e. $y=-f(x-2)+1$
$g(x)=-(x-2)^2+1=-(x^2-4x+4)+1=-x^{2}+4x-3$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$g(x)=-(x-2)^2+1=-x^{2}+4x-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.